Effects of Land Use Change on Land Erosion and Land Critical Level Using GIS in the Mayang Watershed - Mohamad Andhika Rafif; Wiwik Yunarni Widiarti; Entin Hidayah; Saifurridzal Saifurridzal; Mokhammad Farid Ma'ruf (Geosfera Indonesia, 2024)
The increasing population in an area often triggers heightened development, leading to diminished land availability and subsequent land conversion. This transformation, predominantly observed in agricultural and plantation lands, is driven by the need for residential areas. However, continuous land use changes contribute to erosion, a natural process wherein soil is transported, leading to sedimentation and eventual flooding. This study aims to identify critical areas prone to erosion and land degradation. To address this, we used the Universal Soil Loss Equation (USLE) method for erosion prediction, leveraging its simplicity and accuracy. This study focuses on the Mayang watershed in East Java, utilizing a combination of USLE, spectral index modeling, and Geographic Information System (GIS) techniques to estimate soil erosion and land criticality. By integrating methodologies and analyzing data spanning from 2011 to 2021, the study reveals shifts in erosion danger levels and land use patterns. While regions with low erosion remained stable, areas with medium to high erosion declined, yet those with very high erosion exhibited a worrisome increase. Changes in land use, including forest loss and urban expansion, underscore the ecological shifts exacerbating erosion hazards. The study emphasizing the necessity for targeted conservation strategies and comprehensive land management plans to mitigate erosion risks and preserve environmental sustainability.